MiR-135b-5p promotes viability, proliferation, migration and invasion of gastric cancer cells by targeting Krüppel-like factor 4 (KLF4) - Chen, Zhi (Arch Med Sci, 2019)
INTRODUCTION: The expression of MiR-135b-5p was up-regulated while Krüppel-like factor 4 (KLF4) expression was extremely low in human gastric carcinoma (GC) tissues. This study aimed to explore the role of miR-135b-5p in GC cells and its influence on various cell capacity and viability by targeting KLF4. MATERIAL AND METHODS: The dual-luciferase reporter assay was first performed and the target relationship between miR-135b-5p and KLF4 was confirmed. Then three GC cell lines and the human normal gastric epithelial cell line (GES1) were analyzed for the expression level of miR-135b-5p and KLF4 mRNA by RT-qPCR. The BGC-823 GC cell line was chosen for subsequent assays. RESULTS: The expression of miR-135b-5p and KLF4 was manipulated via transfection. The changes of proliferation, invasion, migration, viability, cycle and apoptosis of GC cells were evaluated by MTS, colony formation assay, transwell assay, wound healing assay and flow cytometry assay, respectively. Overexpression of MiR-135b-5p enhanced viability, proliferation, invasion and migration of GC cells, increased cell viability and reduced cell apoptosis. Replenishing of KLF4 functioned oppositely. CONCLUSIONS: The inhibitory effects of ectopic KLF4 could be attenuated by co-transfection of miR-135b-5p. Collective data suggested that miR-135b-5p has a tumor-promoting role in GC cells via downregulating KLF4. Hence, inhibition of miR-135b-5p could be valuable for treatment of gastric cancer.